Perbandingan Model VECN dan ECM dalam Menganalisis Hubungan antara Inflasi dan Indeks Harga Konsumen Bulanan di Kota Bengkulu (2018-2022) - Pahlepi, Reza; Enjelina, Tiara; Aghnia, Haliza; Hidayati, Nurul; Yanti, Rizki Dwi (Diophantine Journal of Mathematics and Its Applications, 2023)
This study compares the effectiveness of Vector Error Correction Model (VECM) and Error Correction Model (ECM) in the context of inflation and consumer price index. The focus of the analysis is on variables that have a long-run relationship even though they are not individually stationary. The VECM model produces . Meanwhile, the ECM Model shows (long-term) and (INFLASI(IHK(Short-term). The results show that VECM is suitable for understanding the short-run and long-run linkages between the variables, while ECM provides more specific insights on the direct effects and long-run equilibrium. A combination or adjustment of the two can provide a comprehensive understanding of the relationship between the variables.